PENGARUH DIVERSIFIKASI PENDAPATAN TERHADAP PROFITABILITAS DAN RISIKO BANK PADA BANK UMUM KONVENSIONAL DI INDONESIA SELAMA PANDEMI COVID-19 - Rahmat Setiawan; Ahmad Naufal Arrafi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the influence between non-interest income and profitability of conventional commercial banks in Indonesia due to the COVID-19 pandemic and to analyze the influence between non-interest income and the risk of conventional commercial banks in Indonesia due to the COVID-19 pandemic. The population in this study are Conventional Commercial Bank companies in Indonesia during the period 2020 quarter I to quarter IV. Data analysis in this study used linear regression assisted by the SPSS program. In this study it is proven that non-interest income (Fee Based Income) has a positive effect on profitability as measured by Return on Asset and Return on Equity and non-interest income (Fee Based Income) has a negative effect on bank risk as measured by Standard Deviation of Return on Asset and Standard Deviation of Return on Equity.